Homonegativity in Britain: Changing Attitudes Towards Same-Sex Relationships. Issue 9 (22nd November 2019) - Watt, Laura; Elliot, Mark
Abstract : Over recent decades, British attitudes towards same-sex relationships have become more accepting. However, results from the National Survey of Sexual Attitudes and Lifestyles show that, in 2010, around a fifth of 16–59-year-olds still viewed sex between two men or two women as 'always wrong'. Using data from each edition of this survey (1990, 2000, 2010), we investigated which individuals are more likely to regard same-sex relationships as wrong and how this has changed over time. Using various measures of individual characteristics, the results showed sex, religiosity, ethnicity, education and whether someone has ever experienced same-sex attraction were most strongly associated with homonegative attitudes. We show that religiosity and ethnicity became more strongly associated with homonegativity between 1990 and 2010, with religiosity replacing education as the characteristic most associated with homonegativity by 2010; explanations for these changes are offered. Further results show that attitudes towards one night stands are also associated with attitudes towards same-sex relationships. This suggests that falling rates of homonegativity might (in part) be explained by a general liberalization in attitudes towards non-traditional sexual relationships.